Analisis Pengaruh Kepemilikan Rumah Oleh Perempuan Terhadap Keberdayannya Dalam Pengambilan Keputusan Rumah Tangga: Analisis Sdki 2017 - Fadhlurrahman, Akmal; Rijal , Hisbi Asyihristani (Jurnal Inovasi Global, 2025)
Women's house ownership has become a significant factor in empowering women with physical resources, enabling them to achieve autonomy in household decision-making. This is particularly relevant given the imbalance in property ownership between men and women, often exacerbated by masculine norms. This quantitative study, using logistic regression, analyzes data from the 2017 Indonesian Demographic and Health Survey. It includes 21,763 female household members aged 15-49 years to determine the impact of home property ownership on the probability of women's involvement in household decisions regarding major asset purchases, visits to relatives, and healthcare. These areas serve as proxies for grassroots women's empowerment. The findings indicate that house ownership has a significant positive influence on women's involvement in household decision-making. Further studies are needed to explore the potential for negative male backlash concerning women's property ownership. Additionally, the importance of empowering women in low-income and middle-income groups should be prioritized.